2002
DOI: 10.1094/phyto.2002.92.10.1038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of a New Phytoplasma Associated with Alfalfa Witches'-Broom in Oman

Abstract: Alfalfa (Medicago sativa) plants showing witches'-broom symptoms typical of phytoplasmas were observed from Al-Batinah, Al-Sharqiya, Al-Bureimi, and interior regions of the Sultanate of Oman. Phytoplasmas were detected from all symptomatic samples by the specific amplification of their 16S-23S rRNA gene. Polymerase chain reaction (PCR), utilizing phytoplasma-specific universal primer pairs, consistently amplified a product of expected lengths when DNA extract from symptomatic samples was used as template. Asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 30 publications
5
48
0
4
Order By: Relevance
“…The possibility of seed transmission has also been investigated following in situ detection of phytoplasma DNA in embryos from coconut palms with lethal yellowing disease [103]. Studies on in vitro growing commercial seedlings of alfalfa (Medicago sativa) firstly showed evidence of seed phytoplasma transmission, data were further confirmed by molecular testing of seedlings from phytoplasma-infected lime (Citrus aurantiaca), tomato (Lycopersicum esculentum), corn and winter oil seed rape maintained in vitro or under insect-proof conditions [104]- [106]. Phytoplasmas can also be efficiently spread via vegetative propagation such as the grafting of infected plant tissues as shoots onto healthy plants, by vegetative propagation through cuttings, and by micropropagation practices and any other method used to multiply plant material that avoids sexual reproduction.…”
Section: Biology and Genomicsmentioning
confidence: 99%
“…The possibility of seed transmission has also been investigated following in situ detection of phytoplasma DNA in embryos from coconut palms with lethal yellowing disease [103]. Studies on in vitro growing commercial seedlings of alfalfa (Medicago sativa) firstly showed evidence of seed phytoplasma transmission, data were further confirmed by molecular testing of seedlings from phytoplasma-infected lime (Citrus aurantiaca), tomato (Lycopersicum esculentum), corn and winter oil seed rape maintained in vitro or under insect-proof conditions [104]- [106]. Phytoplasmas can also be efficiently spread via vegetative propagation such as the grafting of infected plant tissues as shoots onto healthy plants, by vegetative propagation through cuttings, and by micropropagation practices and any other method used to multiply plant material that avoids sexual reproduction.…”
Section: Biology and Genomicsmentioning
confidence: 99%
“…Although 16SrII has been reported in Al-Rhyadih and Al-Hassa provinces in aflalfa and faba bean plants, respectively , the results of this research are considered to be the first report of 16SrII phytoplasma infection in carrot in Saudi Arabia. Phytoplasma group 16SrII was also previously reported to infect faba bean in Sudan (Alfaro-Fernández et al 2012) and alfalfa with little leaf and witches' broom in Iran and Oman, respectively (Khan et al 2002;Hosseini et al 2013). Phytoplasma group 16SrI was associated with alfalfa plants in Bolivia, Lithuania and the USA (Peters et al 1999;Jomantiene et al 2000;Jones et al 2005).…”
Section: Sequences and Phylogenetic Analysismentioning
confidence: 78%
“…Moreover, the age of the field appeared to influence the incidence of the disease in carrot and alfalfa plants. Alfalfa was previously reported to be infected with phytoplasmas in association with witches' broom, yellows and phyllody symptoms, not only in Al-Riyadh, Saudi Arabia (AL-Saleh et al 2014), but also in many other areas around the world, including Italy (Marcone et al 1997), Canada (Khadhair et al 1997), Oman (Khan et al 2002), Bolivia (Jones et al 2005) and Iran (Esmailzadeh Hosseini et al 2015). Leaf reddening, purpling and yellowing; formation of chlorotic adventitious shoots; proliferation and reduction of size and quality of roots were observed in carrot plants infected with phytoplasma in Serbia (Duduk et al 2007), Israel (Orenstein et al 1999), India ), the UK (Nisbet et al 2014), Lithuania (Valiunas et al 2001), Canada (Wally et al 2004) and China (Li et al 2012).…”
Section: Symptoms and Disease Incidencementioning
confidence: 99%
“…Phytoplasma asteris'. Molecular investigations to date have shown phytoplasmas to be associated with cotton phyllody in Italy, Burkina Faso, Mali (Khan et al 2002;Martini et al 2007;Marzachi et al 2009) and luffa witches' broom in Brazil (Montano et al 2007). This is the first record of a phytoplasma associated with both these economically important crops in the Indian subcontinent.…”
mentioning
confidence: 99%